ESTIMATION OF THE GEOLOGICAL STRENGTH INDEX SYSTEM FOR CAVITY LIMESTONE LAYER IN QUARRY AREA, REMBANG, CENTRAL JAVA PROVINCE, INDONESIA - R. Andy Erwin Wijaya; Dwikorita Karnawati; Srijono Srijono; Wahyu Wilopo (Journal of Applied Geology, 2015)
Limestone mining needs a good mine design which is safe for the environment. Mine design is determined by the rock mass quality. The rock mass quality in each mine location is not necessary the same depending on the geological conditions. The research area is located in limestone quarry of Sale District, Rembang Regency, Center Java Province-Indonesia. In the limestone quarry area, there is cavity zone which consists of cavity limestone layer at the wall of quarry bench. This cavity layer in limestone quarry has occurred by solution process. The cavity layer zone is a potentially weak zone which has caused bench failures in the limestone quarry area. The objective of this research is to analyze the rock mass quality in the cavity limestone layer using Geological Strength Index (GSI) system. Final result of the research is a rock mass characterization, specifically for cavity limestone layer. Keywords: geological strength index, limestone, cavity layer